Perancangan Sistem Informasi Kunjungan Pasien Rawat Jalan di Rumah Sakit Muhammadiyah Bandung - Andika Dwi Prayoga; Reza Adila Husaeni Tsabat; Yuda Syahidin; Leni Herfiyanti (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2021)
The purpose of this study was to determine the patient visit information system at this hospital. By using qualitative research methods with a descriptive approach through observation, interviews, and literature studies, while for its development using the waterfall method through the stages of needs analysis, design, coding, implementation, and system testing which is carried out sequentially. This information system was created using Microsoft Visual Studio for databases using Microsoft Access. The problem that occurred in the previous system was that the data processing was still using Microsoft Excel so that the officer's data processing took a long time because it had to be done manually and had not been well integrated. With the information system designed, it is hoped that it can assist officers in processing patient visit data, and can also simplify and speed up officers in making outpatient visit reports because the information system designed is more effective and efficient. The conclusion of this outpatient visit information system design is that the information system is made more integrated and neatly organized.